K–ALJABAR HIPER - Suryoto, Suryoto (MATEMATIKA, 2011)
In this paper will be introduced a form of hyper algebraic structure called a hyper K-algebra and proved the main properties of this algebraic structure. By utilizing the concept of scalar element and simple property of this structure, will be reviewedthe specified forms of this structure and equivalency of them, corresponding to implicative conditions (weak, strong). The discussion only at the structure of hyper algebra of orderthree